(untitled) (Research, Society and Development, 2022)
Treponema pallidum can be transmitted to the fetus through the placenta and cause congenital syphilis (CS). Despite that, few studies have focused on the diagnostic approaches used to analyse congenital syphilis. The aim of this study is to compare the diagnosis methods of CS based on the nested PCR-polA (nPCR), direct immunofluorescence (IF), and histopathology of diverse types of biological specimens obtained from the maternal-fetal interface. A cohort of 103 women and their new-born infants was investigated through the analysis of tissue (placenta and umbilical cord), peripheral blood from the mother and infant, and total blood from the umbilical cord by the methods. The women were determined as having syphilis or not based on a clinical-serological diagnosis. Overall, 29.1% of the women investigated were diagnosed as having syphilis, with 70% being classified as recent cases, and 30% as being in the latent phase. The IF and nPCR procedures were equally effective for the detection of T. pallidum in the tissue of the placenta and umbilical cord, with a positive correlation being observed between the histopathological triad for CS and the identification of the spirochetes. The nPCR was more sensitive for the detection of the treponeme in the samples from the neonates and the umbilical cord. Equivalent results were obtained for the detection of T. pallidum using the nPCR and IF approaches. These techniques provided a valuable addition to the serological diagnosis and histopathological findings, and presented considerable potential for the epidemiological monitoring of SC.